An Atomically Precise Au10Ag2 Nanocluster with Red–Near‐IR Dual Emission. Issue 32 (30th June 2016) - Lei, Zhen; Guan, Zong‐Jie; Pei, Xiao‐Li; Yuan, Shang‐Fu; Wan, Xian‐Kai; Zhang, Jin‐Yuan; Wang, Quan‐Ming
Abstract: A red–near‐IR dual‐emissive nanocluster with the composition [Au10 Ag2 (2‐py−C≡C)3 (dppy)6 ](BF4 )5 (1 ; 2‐py−C≡C is 2‐pyridylethynyl, dppy=2‐pyridyldiphenylphosphine) has been synthesized. Single‐crystal X‐ray structural analysis reveals that1 has a trigonal bipyramidal Au10 Ag2 core that contains a planar Au4 (2‐py−C≡C)3 unit sandwiched by two Au3 Ag(dppy)3 motifs. Cluster1 shows intense red–NIR dual emission in solution. The visible emission originates from metal‐to‐ligand charge transfer (MLCT) from silver atoms to phosphine ligands in the Au3 Ag(dppy)3 motifs, and the intense NIR emission is associated with the participation of 2‐pyridylethynyl in the frontier orbitals of the cluster, which is confirmed by a time‐dependent density functional theory (TD‐DFT) calculation. Abstract : Both kinds of emission : An alkynyl‐protected nanocluster Au10 Ag2 with dual emission in the red–near‐IR region has been synthesized and structurally characterized. The origins of the dual emission bands have been clearly mapped out based on the structures, along with DFT calculations (see figure).